2017
DOI: 10.1093/infdis/jix122
|View full text |Cite
|
Sign up to set email alerts
|

Social and Economic Burden Associated With Typhoid Fever in Kathmandu and Surrounding Areas: A Qualitative Study

Abstract: Typhoid fever is a significant contributor to infectious disease mortality and morbidity in low- and middle-income countries, particularly in South Asia. With increasing antimicrobial resistance, commonly used treatments are less effective and risks increase for complications and hospitalizations. During an episode of typhoid fever, households experience multiple social and economic costs that are often undocumented. In the current study, qualitative interview data from Kathmandu and surrounding areas provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Typhoid fever is frequently fatal when untreated in pediatric or immunocompromised populations [ 9 , 31 , 51 , 79 ]. It affects an estimated 11.9 to 26.9 million people annually [ 6 , 49 , 50 ], with estimated financial burdens equaling roughly a third of the gross national income for patients in undeveloped areas of Southeast Asia [ 35 ]. Current treatments depend on antibiotics; however, STY is rapidly developing antibiotic resistance, thereby increasing both the risk and severity of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Typhoid fever is frequently fatal when untreated in pediatric or immunocompromised populations [ 9 , 31 , 51 , 79 ]. It affects an estimated 11.9 to 26.9 million people annually [ 6 , 49 , 50 ], with estimated financial burdens equaling roughly a third of the gross national income for patients in undeveloped areas of Southeast Asia [ 35 ]. Current treatments depend on antibiotics; however, STY is rapidly developing antibiotic resistance, thereby increasing both the risk and severity of infection.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from Nepal also found that enteric fever patients were concerned about the recurrence of the disease and used supplements and special diets to prevent this. 35 The concerns and awareness regarding relapse or recurrence suggest that it perhaps is more common in the community than the 5–10% hospital-based estimate. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Salmonella typhi is the causative agent of typhoid fever, a serious disease condition with an annual global burden of approximately 16 million cases, leading to 600,000 fatalities [12]. S typhi typically live in animal and human intestines and humans become infected by the consumption of contaminated water or food [12]. S. typhi was reported by 30% of the studies under review as shown in Table 2.…”
Section: Salmonella Typhimentioning
confidence: 99%